Menanamkan Kemandirian Pada Anak Usia 5-6 Tahun Melalui Pembiasaan Sehari-hari - Na'u, Febrianty Fince M; Listyaningrum, Eunike Milasari (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Independence is part of the developmental process that is expected in order to reach maturity. The results of observations in the field showed that there were still children who did not have independent characteristics, one of which was not taking off and putting on their own socks and shoes. This research aims to find out, develop and improve every development in children's independence through daily habits at Bright Minds Day Care by facilitating caregivers in increasing children's independent behavior through daily habits and efforts have been made by Bright Minds Day Care Kanteng Argomulyo, Salatiga City . This research uses a descriptive qualitative approach. The data collection method in this research uses observation, interviews and documentation with descriptive data analysis. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The results of the research show that (1) independence in children is not optimal so that it can be improved through daily habits (2) parents and caregivers lack involvement in increasing children's independence through daily habits